Reviewing the Literature on the Effectiveness of Pressure Relieving Movements. (13th January 2013) - Schofield, Rachel; Porter-Armstrong, Alison; Stinson, May
Abstract : Sitting for prolonged periods of time increases seating interface pressures, which is known to increase the risk of developing pressure ulcers. Those at risk of developing pressure ulcers are advised to perform pressure relieving movements such as "pushups" or "forward leans" in order to reduce the duration and magnitude of pressure acting on the vulnerable ischial tuberosity region. The aim of this review was to synthesize and critique the existing literature investigating the effectiveness of pressure relieving movements on seating interface pressures. The twenty-seven articles included in this paper highlight the need for further research investigating the effect of recommended pressure relieving movements on the pressures around the ischial tuberosities. Furthermore, this review found that the majority of individuals at risk of developing pressure ulcers do not adhere with the pressure relieving frequency or magnitude of movements currently recommended, indicating a need for pressure ulcer prevention to be explored further.